Advances in management accounting. Vol. 26 - Epstein, Marc J.; Malina, Mary A. (Emerald, 2016)
Volume 26 of Advances in Management Accounting examines a broad spectrum of current topics in management accounting.
Keywords: Business & Economics -- Accounting -- Managerial.; Management accounting and bookkeeping.; Accounting.; Managerial accounting.; elektronické knihy; electronic books